What happens in paradise : a novel - Hilderbrand, Elin (New York : Little, Brown & Company, 2019)
A year ago, Irene Steele had the shock of her life: her loving husband, father to their grown sons and successful businessman, was killed in a plane crash. But that wasn't Irene's only shattering news. He'd also been leading a double life on the island of St. John, where another woman loved him, too. Now Irene and her sons are back on St. John, determined to learn the truth about the mysterious life -- and death -- of a man they thought they knew. Along the way, they're about to learn some surprising truths about their own lives, and their futures.
Sequel to: Winter in paradise.
Keywords: Family secrets -- Fiction; Widows -- Fiction; Families -- Fiction; Romance; FICTION / Women; FICTION / Family Life / General; FICTION / Romance / Contemporary; Families; Widows; Widows -- Fiction; Families -- Fiction; Saint John (United States Virgin Islands) -- Fiction; Saint John (United States Virgin Islands) -- Fiction; United States Virgin Islands -- Saint John; Domestic fiction; Fiction; Domestic fiction; Domestic fiction